Java script - Gosselin, Don. (Australia : Course technology, 2009)
JavaScript, Fourth Edition is designed as a guide for beginning programmers to develop Web applications using the JavaScript programming language. It introduces a variety of techniques, focusing on what students need to know to start adding JavaScript to their Web pages. In each chapter, students perform tasks that focus on a particular technique required for building and creating JavaScript programs. The examples and exercises in this book will help students learn the basics of how to use JavaScript with well-formed Web pages, including how to manipulate the browser object model, validate forms, use object-oriented techniques, and learn how to trace and resolve errors in JavaScript programs, to name a few. Advanced topics include how to manage state information, use the Dynamic Object Model (DOM), create Dynamic HTML (DHTML), update Web pages with AJAX, and create server-side scripts.
Includes index.
Keywords: JavaScript (Computer program language).